Effect of interferon treatment on glucose metabolism in children with chronic hepatitis B infection - Zarife KULOĞLU,; Aydan KANSU,; Merih BERBEROĞLU,; Fulya G. DEMİRÇEKEN,; Gönül ÖCAL,; Nurten GİRGİN, (Turkish Journal of Gastroenterology, 2019)
-